Microfluidics for biotechnology - Berthier, Jean, 1952- (Artech House integrated microsystems series., 2010)
"The application of microfluidics to biotechnology is an exciting new area that has already begun to revolutionize how researchers study and manipulate macromolecules like DNA, proteins, and cells in vitro and within living organisms. Now in a newly revised and greatly expanded second edition, the Artech House bestseller, Microfluidics for Biotechnology brings you to the cutting edge of this burgeoning field with three brand-new chapters and a wealth of additional material throughout the book." "Presenting an enlightening balance of numerical approaches, theory, and experimental examples, this book provides a detailed look at the mechanical behavior of the different types of micro/nanoparticles and macromolecules that are used in biotechnology. Professionals gain a solid understanding of microfluidics theory and the mechanics of microflows and microdrops. The book examines the diffusion of species and nanoparticles, including continuous flow and ballistic random walk."--Jacket.